Faktor-Faktor yang Berpengaruh Terhadap Pendapatan Pekerja pada Industri Genteng di Desa Nyitdah Kecamatan Kediri Kabupaten Tabanan - Marbek, I Nengah; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
Industry is an activity to increase welfare in the sense of living for more advanced and higher quality. Industrialization can not be separated from efforts to improve the productivity of human labor and accompanied by efforts to expand the scope of human activity. Expansion of employment targets will be met with increased business activity in the industrial sector. The research was conducted in the village of Kediri Tabanan District Nyitdah. Number of samples taken 83 business units. The purpose of this study was to increase the income of workers in the tile industry in the village of Kediri Tabanan District Nyitdah. The data was collected through structured interviews (questionnaires), indepth interviews and non participant observation. The analysis technique used is multiple linear regression. The results showed simultaneous work experience, hours worked and productivity significantly influence revenue tile artisans in the village Nyitdah Kediri Tabanan District, Adjusted R Square = 0.532, which means 53.2 percent of the income effect of the rise and fall of tile worker in the village of Kediri Tabanan District Nyitdah influenced by work experience, hours worked, and productivity, the remaining 46.8 percent is influenced other variables.
Keywords: pengalaman kerja; jam kerja; produktivitas; pendapatan